PENGELOLAAN KONTEN INSTAGRAM UNTUK MEMPROMOSIKAN SEMANGGI DIGITAL INDONESIA - Aulia Syafira; Rafly Maulana Isyak; Ainur Rochmaniah (MAJU : Indonesian Journal of Community Empowerment, 2026)
The use of social media, especially Instagram, has become an important necessity in digital promotion strategies and has changed the pattern of communication and promotion strategies of companies, making Instagram social media one of the main channels in building brand image and reaching a wide audience. The high number of Instagram users in Indonesia opens up great opportunities for digital companies, including PT Semanggi Digital Indonesia, to optimize promotion through planned and data-driven visual content. However, maximizing the use of Instagram still faces obstacles, especially in terms of content planning, visual consistency, and limited human resources. This community service article discusses Instagram content management assistance at PT Semanggi Digital Indonesia, which involves the student community service team as part of the integration of internship and community service programs. The implementation method was carried out through stages of observation and planning, content production, and evaluation based on Instagram insights.